Ark Shell-Derived Peptides AWLNH (P3) and PHDL (P4) Mitigate Foam Cell Formation by Modulating Cholesterol Metabolism and HO-1/Nrf2-Mediated Oxidative Stress in Atherosclerosis - Chathuri Kaushalya Marasinghe; Jae-Young Je (Marine Drugs)
Atherosclerosis, a leading contributor to cardiovascular diseases (CVDs), is characterized by foam cell formation driven by excessive lipid accumulation in macrophages and vascular smooth muscle cells. This study elucidates the anti-atherosclerotic potential of AWLNH (P3) and PHDL (P4) peptides by assessing their effects on foam cell formation, lipid metabolism, and oxidative stress regulation. P3 and P4 effectively suppressed intracellular lipid accumulation in RAW264.7 macrophages and human aortic smooth muscle cells (hASMCs), thereby mitigating foam cell formation. Mechanistically, both peptides modulated cholesterol homeostasis by downregulating cholesterol influx mediators, cluster of differentiation 36 (CD36), and class A1 scavenger receptor (SR-A1), while upregulating cholesterol efflux transporters ATP-binding cassette subfamily A member 1 (ABCA1) and ATP-binding cassette subfamily G member 1 (ABCG1). The activation of peroxisome proliferator-activated receptor-gamma (PPAR-γ) and liver X receptor-alpha (LXR-α) further substantiated their role in promoting cholesterol efflux and restoring lipid homeostasis. Additionally, P3 and P4 peptides exhibited potent antioxidative properties by attenuating reactive oxygen species (ROS) generation through activation of the HO-1/Nrf2 signaling axis. HO-1 silencing via siRNA transfection abolished these effects, confirming HO-1-dependent regulation of oxidative stress and lipid metabolism. Collectively, these findings highlight P3 and P4 peptides as promising therapeutic agents for atherosclerosis by concurrently targeting foam cell formation, cholesterol dysregulation, and oxidative stress, warranting further exploration for potential clinical applications.